Model Integrasi Fuzzy Servqual-Ipa Dalam Analisis Kualitas Layanan Bandara Supadio - Prihandono, Bayu; Nilamsari Kusumastuti (Pendidikan Matematika Universitas PGRI Yogyakarta, 2025)
Airports serve as strategic transportation nodes that significantly contribute to regional economic development. Ensuring service quality is therefore essential not only for enhancing passenger satisfaction but also for strengthening institutional competitiveness and reputation. Traditional service quality assessments in airports have predominantly relied on quantitative indicators, which are often insufficient to capture subjective and qualitative dimensions such as passenger perceptions and preferences. This study proposes an integrated evaluation framework combining Fuzzy SERVQUAL and Importance Performance Analysis (IPA) to provide a more comprehensive assessment of service quality at Supadio Airport. The Fuzzy SERVQUAL method quantifies passenger satisfaction by addressing the inherent vagueness of human judgment, while IPA identifies critical service attributes requiring managerial attention. Empirical findings indicate that, although the perceived service quality falls short of passenger expectations, the negative gaps remain relatively minor (greater than -5), suggesting that Supadio Airport’s services are approaching the desired standard. The integration of Fuzzy SERVQUAL and IPA not only enhances the robustness of service quality measurement but also generates actionable insights for prioritising improvement strategies. This contribution demonstrates the methodological value of hybrid models in addressing multidimensional service quality issues and provides practical implications for airport management seeking to optimise service delivery and competitiveness. Keywords: Fuzzy Inference, Service Quality, Mass Transportation